Associations between optimism and mental health in postradiotherapy cancer survivors: a cross-sectional survey study - Ka Hei Man; Grace W.K. Ho (BMJ Open)
Objectives Cancer patients often experience psychological distress, while optimism has been identified as a protective factor. However, the mental health of postradiotherapy cancer survivors and its association with optimism remain largely unexplored. This study assesses the mental health status and optimism levels of postradiotherapy cancer survivors and evaluates their associations.Design Cross-sectional survey study.Participants 114 Hong Kong cancer survivors who (1) were aged 18 years or above and (2) had received radiotherapy for their cancer treatment and finished the radiotherapy within the previous 3 years (2021–2024).Outcome measures Mental health was assessed using the Chinese Depression, Anxiety and Stress Scale, and optimism was measured using the Revised Life Orientation Test. Correlation and regression analyses were used to examine the associations between these measures.Results Participants reported overall low optimism with mild to moderate depression, anxiety and stress. Strong negative correlations were identified between optimism and depression (r=−0.833, p<0.01), anxiety (r=−0.767, p<0.01) and stress (r=−0.732, p<0.01). Optimism significantly predicted mental health outcomes in regression models (p<0.001). Gender was also demonstrated as a significant predictor of mental health (p<0.05), with males demonstrating lower optimism and poorer mental health than females.Conclusions This study highlights the importance of incorporating optimism-promoting interventions in postradiotherapy care. Routine optimism screening and gender-specific support are proposed to improve mental health outcomes for radiotherapy patients. While this study provides novel insights into postradiotherapy survivorship, further research should employ longitudinal designs and evaluate intervention effectiveness in clinical settings.